2009 International Conference on Signal Processing Systems 2009
DOI: 10.1109/icsps.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Defect Proneness Using Design Complexity Measurements in Object-Oriented Software

Abstract: Software engineering is continuously facing the challenges of growing complexity of software packages and increased level of data on defects and drawbacks from software production process. This makes a clarion call for inventions and methods which can enable a more reusable, reliable, easily maintainable and high quality software systems with deeper control on software generation process. Quality and productivity are indeed the two most important parameters for controlling any industrial process. Implementatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Indeed, Chidamber and his colleagues stated that DIT is a measure of how many ancestral classes can potentially affect this class, which exactly describes the dependencies of a child class to its ancestors. For this reason, it was reported that higher DIT is associated with higher levels of defect proneness for classes . Many research studies used DIT as a measure of dependency (e.g., ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Chidamber and his colleagues stated that DIT is a measure of how many ancestral classes can potentially affect this class, which exactly describes the dependencies of a child class to its ancestors. For this reason, it was reported that higher DIT is associated with higher levels of defect proneness for classes . Many research studies used DIT as a measure of dependency (e.g., ).…”
Section: Methodsmentioning
confidence: 99%
“…The desire for programming measurements permits the examiners, fashioners, coders, analyzers and the supervisors imagine the product improvement forms and survey the framework [13]. In the item situated environment, one of the significant viewpoints having a solid impact on the nature of coming about programming framework is the configuration many-sided quality [14].…”
Section: Previous Workmentioning
confidence: 99%
“…The data gathered over a longer project duration may reveal different patterns as a decreasing number of components are left unchanged. [2] Many other methods are described to identify and visualize class interactions that are the most change-prone. That method was object-oriented software developed using design patterns [3].…”
Section: Related Workmentioning
confidence: 99%